(untitled) (Aura: Journal for the Study of New Religions, 2021)
While meditation has undeniably become a part of popular culture, the term encompasses a wide variety of practices and conceptualizations on the religious-secular spectrum. In this paper, I explore how this wide scope is dealt with at meditation retreats offered at the Norwegian center Dharma Mountain. The place is built around the Norwegian guru Vasant Swaha and serves as a meeting place for his disciples, the sangha. At the same time, the Dharma Mountain group takes part in the wider popular meditation field with retreats tailored toward the preferences of an often guru-critical mainstream audience. Based on ethnographical material, I compare two meditation techniques, vipassana and Dynamic Meditation, and how they are introduced, legitimized, and performed at a newcomer weekend in the first and a summer retreat with Vasant Swaha in the second case. I show that while instructors introduce vipassana as a generic and simple technique, they mark Dynamic Meditation as a specifically composed method and thus integrate it with Swaha’s background in the Osho movement and the therapeutic outlook of his retreats. My findings point to the flexibility of the concept of meditation and how this helps organizers to address different audiences. Under the umbrella of meditation, Dharma Mountain incorporates a range of conceptualizations, from self-help to spiritual awakening, and different social forms, from costumer relations to religious community, in one and the same place.